Effects of SMILE Surgery on Intraocular Pressure, Central Corneal Thickness, Axial Length, Peripapillary Retinal Nerve Fiber Layer, and Macular Ganglion Cell Complex Thickness - Zhanlin Zhao; Sylvain Michée; Jean-François Faure; Christophe Baudouin; Antoine Labbé (Journal of Ophthalmology)
Purpose. To evaluate the change in intraocular pressure (IOP), central corneal thickness (CCT), axial length, peripapillary retinal nerve fiber layer (RNFL) thickness, and macular ganglion cell complex (GCC) thickness after small incision lenticule extraction (SMILE) surgery. Methods. This prospective observational study was conducted in Espace Nouvelle Vision, Ophthalmological Clinic, Paris, France. Fifty eyes of 25 patients were enrolled in this study and underwent SMILE surgeries. IOP, central corneal thickness (CCT), axial length (AL), peripapillary RNFL thickness, and macular GCC thickness were measured before and at 3 months after SMILE. Results. The mean preoperative spherical equivalent was −3.15 ± 1.50 diopters (D), and the mean postoperative value was 0.15 ± 0.28 D. After SMILE surgery, IOP decreased from 15.03 ± 2.79 mmHg to 11.02 ± 2.73 mmHg and 10.02 ± 2.21 mmHg at 1 and 3 months, respectively (P<0.01 for both comparisons). The mean decrease in measured IOP as a function of ablation depth was 0.065 ± 0.031 mmHg/μm. CCT decreased from 545.98 ± 26.61 μm to 478.40 ± 30.26 μm after SMILE surgery (P<0.01). AL decreased from 24.80 ± 0.84 mm to 24.70 ± 0.83 mm (P<0.01). There was no statistically significant change in mean peripapillary RNFL or mean GCC thickness after SMILE surgery. Conclusions. SMILE surgery modified IOP measurement, CCT, and AL but did not change peripapillary RNFL and macular GCC thicknesses. The postoperative drop in measured IOP might be explained by the decreased CCT. An accurate re-evaluation of AL should be performed before cataract surgery among post-SMILE patients.